Mycotic Arterial Aneurysm - Islam, Shariful; Harnarayan, Patrick; Naraynsingh, Vijay (Issues and Developments in Medicine and Medical Research Vol. 10, 2022)
A mycotic aneurysm is a very rare infection of the vessel wall associated with high morbidity and mortality. Although rare, the incidence of mycotic aneurysms is slowly increasing over the last two decades due to an increase in risk factors of atherosclerosis and immunosuppression. The infection may be bacterial, viral, or fungal in origin. The pathogenesis is complex with a combination of risk factors. It has a fulminant course. It usually presents as a diagnostic and therapeutic challenge to the General and Vascular Surgeon due to the non-specific nature of the clinical presentation as well as the lack of clear diagnostic criteria. Prompt diagnosis and treatment are of paramount importance for a successful outcome. Treatment depends on the type of invasive interventions, patient’s underlying comorbid conditions, sites of involved vessels as well as the type of facility and skill settings available at that institution. Conservative treatment is usually associated with high mortality. Surgical intervention in combination with prolonged antimicrobial therapy is the key therapeutic option. A coordinated effort amongst the team members of various specialties is important for a successful outcome. This chapter aims to highlight the role of the multi-disciplinary team in evaluating and treating these patients and up-to-date literature review; to identify the exact etiology, presenting features, appropriate evaluation procedures, up to date therapeutic options for a suspected mycotic arterial aneurysm.